Alpha-glucosidase inhibitor decreases the risk of colorectal adenoma in the aged with Type 2 diabetes - Dingchao Xia; Lanling Jin; Binfeng Wang; Yi Jin; Qun Zheng; Jie Xu; Senzhong Chen (Scientific Reports)
Abstract The rapidly aging population is fueling a surge in diabetes, especially Type 2, which heightens colorectal cancer (CRC) risk. Colorectal adenoma, a precursor, compounds this trend. Although alpha-glucosidase inhibitors are effective hypoglycemic drugs working in the GI tract, the link between them and colorectal adenoma formation remains unexplored. A retrospective cross-sectional study was conducted on type 2 diabetes patients aged 60 and above using data from Wenzhou Central Hospital from January 2021 to May 2024. We used multivariable logistic regression and propensity score matching analysis (PSM) to calculate adjusted ORs for colorectal adenoma, controlling for potential confounders. A total of 311 subjects were enrolled in the study, with a mean age of 67.55 years. 138 (44.4%) were diagnosed with colorectal adenoma. Multivariate logistic regression analysis revealed that the AGI (Alpha-glucosidase inhibitor) Group had an adjusted OR of 0.399 (95% CI = 0.22–0.723, p = 0.002) compared to those with AGI free people. A similar trend was also observed in the PSM analysis (OR = 0.362, 95% CI = 0.176–0.744, p = 0.004). Subgroup analysis reveals hypertension as a potential modulator of the inverse relationship between AGI and colorectal adenoma occurrence post-PSM (p = 0.049). And AGI reduces serum iron levels, both before (p = 0.01) and after PSM (p = 0.028). In summary, our findings indicate that AGI significantly mitigates the risk of colorectal adenoma among individuals aged 60 and above, particularly among those afflicted with hypertension. Additionally, it substantially decreases serum iron levels.